Rezensionen - Scheer, Matthias K.; Bälz, Moritz (Zeitschrift für Japanisches Recht, 2000)
Wolfgang Hadamitzky, Japanese, Chinese and Korean Surnames and How to Read Them. 275 Oliver Tieste, Karôshi, ein japanisches Phänomen? 277 Akira Kawamura (Hrsg.), Law and Business in Japan. 279 Luke Nottage / Leon Wolff: Japanese Section in: World Dictionary of Legal Abbreviations 282